COMPLIANCE OF POLRI MEMBERS WITH THE ENFORCEMENT OF THE STATE POLICE PROFESSIONAL CODE OF ETHICS OF THE REPUBLIC OF INDONESIA - Setio, Dedy (UNES Law Review, 2023)
The Indonesian National Police has the capacity to maintain peace in society. Police agencies have an obligation to act as a driving force for the creation of security and order in people's lives. The existence of police agencies is required to be able to overcome various problems that exist in society, especially the problem of compliance with police officers in enforcing the police professional code of ethics towards optimizing police member compliance. This research method is normative research by using statutory and conceptual approaches as a basis for answering these problems. The conclusion is that the enforcement of the police professional code of ethics is due to the weak internal control carried out by the police agency on all of its members. This weak internal oversight has caused many cases of violations of the police professional code of ethics to emerge. The efforts of the Indonesian National Police in improving its internal affairs must be able to uphold the law without violating the professional code of ethics. So that the formation of disciplinary regulations for POLRI members aims to increase and maintain credibility and unwavering commitment. The credibility and commitment of members of the National Police are as state officials who are given the task and authority as protectors, protectors and public servants, as well as law enforcers and maintaining security.